STRATEGIC RESPONSES TO ASYMMETRIC THREATS: A Study of COIN, CT, and CI Tactics in Papua - Sarjito, Aris (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study assesses the effectiveness of counterinsurgency (COIN), counterterrorism (CT), and counterinsurgency (CI) tactics in addressing asymmetric threats in Papua. Utilizing qualitative research methods, secondary data from existing literature, case studies, and expert opinions were synthesized. The research aimed to understand the challenges faced by security forces in implementing strategic responses and propose recommendations to enhance effectiveness. Findings revealed the mixed effectiveness of current tactics, hindered by terrain complexity, logistical constraints, resource limitations, and coordination issues. The study recommends a comprehensive approach, integrating community engagement, development assistance, interagency cooperation, and conflict resolution initiatives.